FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KINERJA KADER JUMANTIK PADA MASA PANDEMI COVID-19 DI WILAYAH KERJA UPTD PUSKESMAS I DINAS KESEHATAN DENPASAR SELATAN TAHUN 2022 - I G. A. Pramesti Suari; I Gusti Ayu Made Aryasih; I Wayan Sali; I Nyoman Sujaya (Poltekkes Kemenkes Denpasar, 2023)
Jumantik (community partisipation in dengue prevention) has an important role in controlling dengue hemorrhagic fever in an area. During the COVID-19 pandemic, Jumantik's performance was adjusted to the community's COVID-19 cases. This study aims was to analyze the relationship between age, gender, education level, level of knowledge about DHF Prevention, perception of the risk of COVID-19 infection, appropriateness of Jumantik honorarium, leadership support and performance of jumantik cadres during the COVID-19 pandemic in the working area of Puskesmas I South Denpasar in 2022. This was an observational study with a cross sectional design. The number of respondents was 39 jumantik with the measurement instrument using a questionnaire. The results showed that there was no relationship between gender (p = 0.328) and age (p = 0.169) with the performance of jumantik cadres at Puskesmas I South Denpasar during the COVID-19 pandemic in 2022. Meanwhile, there was a relationship between education level (p = 0.001) knowledge (p= 0.001), honorarium compatibility (p= 0.007), leadership support (p= 0.001), with the performance of jumantik cadres at UPTD Puskesmas I South Denpasar Health Service during the COVID-19 pandemic in 2022. Based on research the researcher suggest to conducting training and preparing PPE for jumantik during the COVID-19 pandemic.